Modification of the Fitzpatrick system of skin phototype classification for the Indian population, and its correlation with narrowband diffuse reflectance spectrophotometry. (10th January 2018) - Sharma, V. K.; Gupta, V.; Jangid, B. L.; Pathak, M.
Summary: Background: The Fitzpatrick classification for skin phototyping is widely used, but its usefulness in dark‐skinned populations has been questioned by some researchers. Recently, skin colour measurement has been proposed for phototyping skin colour objectively. Aims: To modify the Fitzpatrick system of skin phototyping for the Indian population and to study its correlation with skin colour using narrowband diffuse reflectance spectrophotometry Methods: Answer choices for three items (eye colour, hair colour, colour of unexposed skin) out of 10 in the original Fitzpatrick questionnaire were modified, followed by self‐administration of the original and the modified Fitzpatrick questionnaire by 70 healthy Indian volunteers. Skin colour (melanin and erythema indices) was measured from two photoexposed and two photoprotected sites using a narrowband reflectance spectrophotometer. Results: The mean ± SD scores for the original and modified Fitzpatrick questionnaires were 25.40 ± 4.49 and 23.89 ± 4.82, respectively ( r = 0.97, P < 0.001). The two items related to tanning habits were deemed irrelevant based on the subjects' response and were removed from the modified questionnaire. The Melanin Index (MI) of all sites correlated moderately well with both the modified ( r = 0.61–0.64, P < 0.001) and original Fitzpatrick questionnaire scores ( r = 0.64–0.67, P < 0.001), while the Erythema Index showed poor correlation with both. An MI value of ≧ 42 was found to be the cut‐off between skin phototypes I–III and IV, and ≥ 47 between IV and V–VI. Conclusions: Our modification of the Fitzpatrick questionnaire makes it more relevant to the Indian population. Spectrophotometry can be a useful objective tool for skin phototyping.